Islamic financing for small medium enterprises: Challenges and opportunities - Muhmad, Siti Nurain; Wan Ismai, Wan Nur Syahida; A Rahim, Nurul Aisyah Awanis; Ahmad, Sarah Nadia (Othman Yeop Abdullah Graduate School of Business, 2020)
This study attempts to discuss the challenges and opportunities of Islamic financing for Small Medium Enterprise (SMEs), as the Islamic finance industry's growth and SMEs are stimulated in this recent year. The government has introduced Islamic SME financing since 2012, and Malaysia has promoted it by granting a rebate for the participated parties, especially Islamic financial institutions. However, the government's opportunities are still in the slow mode to be grabbed by SMEs. With selected literature related to SMEs and Islamic financing, this study discussed SMEs and Islamic banks' practices in Malaysia. Based on the literature, several issues had to be highlighted, such as SMEs' readiness to have the opportunity with larger firms, SMEs' behaviours, and attitudes when dealing with external supports, as well as their awareness of business financing. Thus, this study highlights the challenges and real issues among SMEs and points out the opportunities for improvement that are expected to benefit SMEs and Islamic financial institutions in Malaysia.